Animasi 2D Brand “Sate Manangkabau” Di Kota Padang (International Forum of Researchers and Lecturers, 2023)
Sate Manangkabau is a brand engaged in the culinary field in the city of Padang, West Sumatra. This brand was created in August 2018. In the current era of global competition, rapidly growing market increases, increasing technology, as well as the challenges of competition for each brand require each brand to innovate and be creative in developing appropriate promotional strategies. The purpose of this work is to present a 2d animated promotional advertisement for the Sate Manangkabau brand in order to maintain the existence of the brand that has been formed and as a unique and innovative promotional medium that can attract the attention of consumers. The design method for the 2D Animation Brand